Characteristics And Mineral Content of Lampung Tengah Ironsands - Deska Lismawenning Puspitarum; Gita Safitri; Harlina Ardiyanti; Mohamad Samsul Anrokhi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Characteristics and Mineral Content of Lampung Tengah Ironsands. This study is carried out to investigate the characteristics and mineral content of ironsands from Bekri, Lampung Tengah Regency by using precipitation method. The research was conducted in Physics Laboratory of Institut Teknologi Sumatera from June to September 2018. Mineral content of sand is analayzed with X-Ray Diffractometer. The extraction was varied in temperature and stirring time. The temperature is varied in 80oC, 120oC, dan 160oC and yields different size; 33.76 nm, 11.84 nm and 11.14 nm. Meanwhile, the extraction is varied for 2 hours, 4 hours and 6 hours stirring and yields particle with 43.12 nm, 11.14 nm and 11.32 size. Mineral content of ironsands in Lampung Tengah are dominated by Ilmenite and Potassium Chloride.